Post-traumatic Submandibular Haematoma in an Eight-year-old: A Case Report - Mansi Sharma; Anil Gupta; Shalini Garg; Vishal Sharma; Shweta (Journal of Clinical and Diagnostic Research)
A haematoma is a collection of blood and blood components under the skin’s subcutaneous layer. An acute wound to the blood vessel wall is a frequent cause of haematomas. Focal swelling, taut skin and soreness are associated with blood expanding and pooling beneath the skin. It can be difficult to diagnose if there is an underlying discolouration. The authors report a case of an eight-year-old female patient with the chief complaint of swelling on the face for two days due to a fall from a height of 10 feet. She reported a history of blood from the mouth and avulsed upper lateral incisors immediately after the fall. Bilateral diffuse swelling was observed in the submandibular region, measuring 7×7 cm extraorally, extending from the inferior border across the midline and from the chin to the hyoid bone, accompanied by facial asymmetry. The final diagnosis was post-traumatic haematoma and a conservative approach was the treatment of choice. The present case highlights the importance of correct diagnosis and early intervention.